Measurement and Correlation of the Viscosity of Water-Based Al2O3 and TiO2 Nanofluids in High Temperatures and Comparisons with Literature Reports - Yiamsawas, Thaklaew; Dalkilic, Ahmet Selim; Mahian, Omid; Wongwises, Somchai (TAYLOR & FRANCIS INC, 2013)
In this article, the viscosity of two common nanofluids including Al2O3/water and TiO2/water is measured at high temperatures, and high concentrations of the nanofluids. The range of temperature is 15-60 degrees C where the volume fraction of nanoparticles varies from 1 to 8%. Next, comparisons have been done with the most well-known theoretical and experimental reports in the literature. Finally, using the experimental data, a helpful correlation is presented.
Keywords: Correlation; high temperature; nanofluid; viscosity; THERMAL-CONDUCTIVITY; HEAT-TRANSFER; VELOCITY-FIELD; GLYCOL; Chemistry